Solve the pair of linear equations (a+b)x + (a-b)y = a^2+b^2 (a-b)x + (a+b)y = a^2+b^2​

Question

Solve the pair of linear equations

(a+b)x + (a-b)y = a^2+b^2

(a-b)x + (a+b)y = a^2+b^2​

in progress 0
Hadley 5 months 2021-12-21T19:22:14+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-12-21T19:23:17+00:00

    Step-by-step explanation:

    (a−b)x+(a+b)y=a

    2

    −2ab−b

    2

    —– (i)

    (a+b)(x+y)=a

    2

    +b

    2

    ——– (ii)

    Subtracting eq (i) by eq (ii), we get.

    ⇒(a−b)x−(a+b)x=a

    2

    −2ab−b

    2

    −a

    2

    −b

    2

    ⇒−2bx=−2bx(a+b)

    ⇒x=(a+b)

    ∴(a+b)(a+b+y)=a

    2

    +b

    2

    ⇒(a+b)

    2

    +(a+b)y=a

    2

    +b

    2

    ⇒y=

    a+b

    −2ab

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )